Determinação da atividade da pectina metilesterase em pectinases industriais e a atividade residual exógena no suco da manga - Gonzalez, Samantha Lemke (2009)
Pectinases, a group of enzymes that degrade pectic substances and break glycosidic linkages, are produced by fungi, yeasts and bacteria, but are also in plants in general and fruit in particular.In the juice industry the pectinolytic enzymes are added to increase the efficiency of the process, decrease the viscosity and reduce the time of filtration. The pectin methylesterase, PME, hydrolyzes the methyl ester groups, forming carboxyl groups in pectin chain, releasing methanol end H3O+. Therefore, its knowledge is vital in order to control the effectiveness of the treatment. The purpose of this study was to determine the optimum conditions of the activity of the pectin methylesterase in industry preparations, proposing a potentiometric procedure for determining the PME activity and compare the data with those obtained by traditional potentiometry and Uv-Vis, evaluate the efficacy of this method in determining the residual activity exogenous of PME in mango juice. The activity of PME in the three commercial samples, Pectinex 100L Plus, Panzym Univers and Panzym Clears, was determined by potentiometry, Uv-Vis spectroscopy, with the bromophenol blue indicator, and the action of alcohol oxidase with acetyl acetone. The reaction consisted of 5.00 mg.mL-1 apple pectin, 0.100 mol.L-1 sodium chloride and 50 μL commercial pectinolytic enzyme for a volume of 30 mL. In all experiments the enzyme deesterification showed first-order kinetics, with increased activity at pH 4.0 to 4.5 and 45 ºC, whereas the complete inactivation occurred at 75 ºC for 10 minutes, in the three industrial preparations. The thermal inactivation of the PME of Pectinex 100L Plus and Panzym Clears preparations occurred under the same conditions, when the activity was measured by the procedures of ΔVNaOH / Δttime or of ΔpH/ Δttime. The activity of PME in industrial preparations at 25 °C and pH 4.5, determined by UV-Vis spectroscopy with bromophenol blue indicator, showed good correlation with the activity determined by the procedures by potentiometry. The stability of the indicator in the pectin solution allows its use to determine the PME activity in samples in which the optimum pH is located in acid band. The release of methanol as measured by alcohol oxidase, followed by the reaction with acetyl acetone to determine the formaldehyde, showed good agreement with the results of the enzyme activity measuring procedures used in this research. The inactivation of residual PME in mango juice occurred at 75 ºC for 20 minutes of exposure in the procedure ΔVNaOH / Δttime and 10 minutes of exposure during the procedure ΔpH/ Δttime. The residual activity of PME in 70 °C for 10, 20 and 30 minutes of exposure in the presence of juice was higher than in the control, indicating its protective effect. The procedure of ΔpH/ Δttime shows good correlation with other methods, with the advantage of precise and direct measures of [H+], excusing a series of reagents and high costs materials.